HEADS AND TAILS REVISITED - Vasantkumar, Chris (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2016)
This research report revisits Keith Hart’s work on the mutual implication of token and commodity theories of money, focusing on his classic Malinowski lecture on the coin’s two sides. Hart associates ‘heads’ with political authority and token theories and ‘tails’ with quantitative value, market exchange and commodity theories. Yet, even as he argues for the necessity of a rapprochement between the intellectual approaches delimited by the coin’s two sides, the coin conceit as he elaborates it is unprepared to deal with the quotidian intermixing of ‘heads’ and ‘tails’ one encounters in actual rather than theoretical coinage. Starting from the problems posed by actual coins to the apparent clarities of Hart’s coin, this essay argues that on a material, micro-level the relationships between state power and market exchange on the one hand and ‘heads’ and ‘tails’ on the other are rather more contingent in practice than in theory. On this level, actually-existing forms of Western money are only poorly parsed by the ‘sidedness’ of the coin conceit. The a priori divisions between power and quantification, symbols and amounts, as well as their topological mapping onto discretely divided material surfaces freighted in the virtualism of ‘heads’ and ‘tails’ are a poor fit with complex amalgams of numbers, power, states, symbols and exchange we may read off the surfaces of particular coins.